The Role of the FAO in Reducing Migration Pressures and Implementing Sustainable Development Goals (Zero Hunger) - Untari Narulita Madyar Dewi (Insignia: Journal of International Relations, 2021)
This research article will describe how food security and the issue of international migration are interrelated. The advances of communication and transportation technology have encouraged the movement of people in one country to carry out international migration in other countries. Various factors drive people to international migration, one of the reasons is the impact of conflict. Migrating to a safer and more peaceful country does not mean it will guarantee their survival. Another problem arises, one of which is related to food security. Based on this issue, the authors asked the research question: How the role of the World Organization FAO (Food and Agriculture Organization of the United Nations) in reducing migration pressures and implementing sustainable development goals number two (zero hunger). In this paper, the writer uses qualitative research methods. The results of this study are 1) FAO addresses the root causes and driving factors of migration, 2) Helps create job opportunities in agriculture and off-farm for young generations, women, and those who intend to migrate, 3) Develop sustainable strategies so that refugees can integrate with the society that accepts them. The conclusion and research are that migration should be an option, not a necessity. The sustainable development program goal zero hunger forms the basis of the FAO initiative to make a positive contribution to migrants.